2021
DOI: 10.1007/s11947-021-02611-4
|View full text |Cite
|
Sign up to set email alerts
|

Continuous High-pressure Cooling-Assisted Homogenization Process for Stabilization of Apple Juice

Abstract: The effect of high-pressure homogenization (HPH) at 100–200 MPa (with up to 5 passes) on the quality and storage stability of apple juice was investigated. The microbiological quality, polyphenol oxidase (PPO), peroxidase (POD), polygalacturonase (PG) and pectinmethylesterase (PME) activity, particle size distribution (PSD), apparent viscosity, turbidity, concentration of vitamin C, individual polyphenols and their total content (TPC), antioxidant activity, and colour of fresh, HPH-treated apple juice were all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 67 publications
3
14
1
Order By: Relevance
“…For what concerns color parameters, HPH increased a* and b* values while it decreased the L* value. The overall ΔE was 6.8 CIELAB units, in line with what was reported by Szczepańska et al [ 34 ], considering the high variability observed in our study. The effect of HPH on juice color seems strongly dependent on food matrices and treatments.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For what concerns color parameters, HPH increased a* and b* values while it decreased the L* value. The overall ΔE was 6.8 CIELAB units, in line with what was reported by Szczepańska et al [ 34 ], considering the high variability observed in our study. The effect of HPH on juice color seems strongly dependent on food matrices and treatments.…”
Section: Discussionsupporting
confidence: 93%
“…As already demonstrated in many publications [ 17 , 34 , 35 , 36 ], HPH treatment at 150 MPa reduces the naturally occurring microflora present in vegetable juice. In this study, a reduction ranging between 1.0 and 2.4 log cycles was observed for TMC depending on the number of HPH passes and inlet temperature of the treated juice.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This result supports the high efficiency of UHPH controlling bacteria in grape juices compared with discontinuous pressurisation techniques, such as HHP, which is unable to eliminate them completely, even at pressures higher than 500 MPa/10 min (Morata et al, 2015). Also, UHPH is much more efficient than HPH, which normally needs multi-passes to reach inactivation lower than 2-log at 200 MPa (Szczepańska et al, 2021). Saccharomyces yeast starters were inoculated in both the control and UHPH musts at 5 × 10 7 CFU/mL, and the population of Saccharomyces and non-Saccharomyces yeasts was monitored every two days.…”
Section: Microbial Loadssupporting
confidence: 67%
“…Several recent reviews have included the most important features and applications of UHPH processing (Comuzzo & Calligaris, 2019;Patrignani & Lanciotti, 2016;Zamora & Guamis, 2015). UHPH is more efficient than high-pressure homogenisation (HPH) or microfluidisation concerning the elimination of microorganisms and enzyme inactivation, which normally needs multi-passes for efficient microbial control (Szczepańska et al, 2021). Additionally, HPH or microfluidisation are used to improve colloidal stability (Leite et al, 2016;Oliete et al, 2019); however, UHPH produces nanofragmentation, with lower than average size particles stabilising better colloidal structure .…”
Section: Introductionmentioning
confidence: 99%